Piezoresistive, Surface Contact, Carbon-Polymer Composite Sensors - DAVID O'CONNOR (2023)
Printed, thin-film, flexible, polymer composite force sensors afford the opportunity for spatial mapping with a small form factor on a flexible substrate. The piezoresistive responses of printed, dual-substrate, nano-carbon sensors were investigated up to 2 kN in compression with multiple configurations and materials. Clarification of the dominant piezoresistive mechanism and development of real world applicationswas sought after. The sensor topology and bulk materials revealed clustersof thin-film graphite platelets (⪅ 20μm) percolating within the bulk, and producingelectrically conductive asperities at the contact surface, which was confirmedby detailed chemical and morphological characterisation. The dominant piezoresistivemechanism was linked to the conductive surface contact area between thetwo substrates as the surfaces deformed, when subject to a compressive load. Thepiezoresistive response was altered by varying the conductive particle loading of theinks from 0 to 7% by volume fraction, along with a simplified surface contact modelpresented to predict the response. A new ink and methodology was developed tocoat carbon fibres, producing a flexible piezoresistive sensor fibre, for integrationinto a fibre reinforced composite panel. This new configuration takes advantage ofthe dual-substrate surface contact mechanic of the sensor architecture by allowingeach sensor fibre (one substrate of the dual-substrate architecture) to be woven intoa piece of cloth and then placed in contact to another similarly woven cloth withina typical fibre composite layup, to create an integrated sensor matrix at no additionalmanufacturing cost for the assembly of the composite panel. Fibre reinforcedpanels containing addressable integrated sensor networks embedded demonstratesthe ability to develop smart structural composites, and the opportunity to furtherdevelop wearable technology via a woven sensor fibre fabric.